Metabolic profile during exhaustive arm stroke, leg kick and whole body swimming lasting 15 s to 10 min. - Ogita, F.; Onodera, T.; Tamaki, H.; Toussaint, H.; Hollander, P.; Wakayoshi, K. (Biomechanics and Medicine in Swimming IX, 2003)
AIM: This study aimed to measure the duration depending metabolic demands elicited by arm stroke (A), leg kick (K) as well as whole body stroke (S). METHODS: The subjects were 6 well-trained college male swimmers (21± 1 yrs). Experiments were carried out in a swimming flume. The subjects swam at six different water flow rates, which were estimated to cause exhaustion in 15 s, 30 s, 1 min, 2-3 min, 4-5 min, and 8-10 min, with each stroke. Also, the accumulated O2 uptake (AOU) and the accumulated O2 deficit (AOD) were determined in all bouts. RESULTS: The AOU increased linearly with exercise duration in all strokes, and the increase rate of AOU in A and K corresponded to 70, and 80 % in S, respectively. The AOD in A and S significantly increased until 2-3min exercise with the increase in duration, while the AOD in K more rapidly increased and the AOD at 30s was not significantly different from those at 1 min and 2-3min. The AOD gradually decreased when the exercise duration was a longer than 4-5min. The relative importance of anaerobic energy processes in three strokes decreased from 78-80 % for 15 s to 50 % for 1 min, 30 % for 2-3 min, 5 % for 8-10 min duration. The anaerobic importance in K was greater than those in A and S until 30 s duration. DISCUSSION: These results suggest that the metabolic demands of exhaustive bouts lasting 15 s to 10 min is comparable in A and S, but that the importance of anaerobic energy processes in K would be greater during bout shorter than 30 s when compared to A and S. Therefore, when the training is performed for the purpose of improving the anaerobic capacity, the swimmers and coaches should make the training program, considering that the exercise duration and thus the exercise intensity to give the maximal stimulus for anaerobic energy process in K are different from those in A and S.